2018
DOI: 10.1155/2018/2175927
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Galectins in Cervical Cancer Biology and Progression

Abstract: Cervical cancer is one of the malignant tumors with high incidence and high mortality among women in developing countries. The main factors affecting the prognosis of cervical cancer are the late recurrence and metastasis and the effective adjuvant treatment, which is radiation and chemotherapy or combination therapy. Galectins, a family containing many carbohydrate binding proteins, are closely involved in the occurrence and development of tumor. They are involved in tumor cells transformation, angiogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 121 publications
1
34
0
Order By: Relevance
“…Furthermore, similar results were obtained in ICC studies that level of LGALS1 expression was significantly elevated in SiHa and C33A cell lines comparing to normal epithelial cells of cervix. Therefore, these findings together with previous reports strongly suggest that LGALS1 is overexpressed in cervical cancer cells [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, similar results were obtained in ICC studies that level of LGALS1 expression was significantly elevated in SiHa and C33A cell lines comparing to normal epithelial cells of cervix. Therefore, these findings together with previous reports strongly suggest that LGALS1 is overexpressed in cervical cancer cells [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Heart disease acute heart failure plasma level combination with natriuretic peptide [62] acute heart failure plasma level promising prognostic marker [63] chronic heart failure plasma level useful in HF patients with preserved LVEF [64] chronic heart failure myocardial and plasma level not associated with histology [65] acute myocardial infarction serum level no definite relationship with ventricular remodeling [66] Nervous system diseases myelin degeneration tissues activation of the phagocytosis of degenerated myelin [42] intracerebral hemorrhage plasma level prognostic predictor [67] subarachnoid hemorrhage plasma level prognostic predictor [68] global brain ischemia cerebrospinal fluid prognostic marker and inflammatory mediator [69] Renal disease CKD plasma level associated with progression of CKD [25] SLE nephritis serum and biopsy specimens associated with SLE patients, particularly in SLE nephritis [70] Liver disease liver fibrosis serum Gal-3 related binding protein assessing liver fibrosis [71] Connective tissue diseases rheumatoid arthritis serum level increased in early rheumatoid arthritis [72] SLE serum anti-Gal-3 antibody a key role in SLE skin lesions [73] systemic sclerosis serum level predictor of mortality [74] Neoplasms colorectal cancer serum and tissues related to tumor progression [52] breast cancer human cell lines important factor for treatment [75] non-small cell lung cancer tumor expression promotion of invasion and metastasis [76] lung and prostate cancers tumor expression therapeutic target of tumor immunity [77] cervical cancer tumor expression targets of multifunctional cancer treatment [78] thyroid cancer tumor expression diagnostic marker [79]…”
Section: Diseasesmentioning
confidence: 99%
“…Previous studies have confirmed that the sustained high-risk human papillomavirus (HPV) infection is the prerequisite for the initiation and progression of cervical cancer [2]. The conventional treatments for cervical cancer are surgery, radiotherapy, chemotherapy and molecular targeted therapy [3]. Radiotherapy remains the mainstay of treatment, especially in advanced cervical cancer [4].…”
Section: Introductionmentioning
confidence: 99%